HbA1c Measurement Improves the Detection of Type 2 Diabetes in High-Risk Individuals With Nondiagnostic Levels of Fasting Plasma Glucose - Rachel Perry; R. Ravi Shankar; Naomi Fineberg; Janet B. McGill; Alain Baron (2001)
OBJECTIVE—Whereas new diagnostic criteria based on a fasting plasma glucose (FPG) of >126 mg/dl (7.8 mmol/l) have improved the detection of diabetes, multiple reports indicate that many people with diabetes diagnosed by 2-h oral glucose tolerance test (OGTT) glucose measurements of ≥11.1 mmol/l (200 mg/dl) would remain undiagnosed based on this FPG criteria. Thus, improved methods to detect diabetes are particularly needed for high-risk individuals. We evaluated whether the combination of FPG and HbA1c measurements enhanced detection of diabetes in those individuals at risk for diabetes with nondiagnostic or minimally elevated FPG. RESEARCH DESIGN AND METHODS—We analyzed FPG, OGTT, and HbA1c data from 244 subjects screened for participation in the Early Diabetes Intervention Program (EDIP). RESULTS—Of 244 high-risk subjects studied by FPG measurements and OGTT, 24% of the individuals with FPG levels of 5.5–6.0 mmol/l (100–109 mg/dl) had OGTT-diagnosed diabetes, and nearly 50% of the individuals with FPG levels of 6.1–6.9 mmol/l (110–125 mg/dl) had OGTT-diagnosed diabetes. In the subjects with OGTT-diagnosed diabetes and FPG levels between 5.5 and 8.0 mmol/l, detection of an elevated HbA1c (>6.1% or mean + 2 SDs) led to a substantial improvement in diagnostic sensitivity over the FPG threshold of 7.0 mmol/l (61 vs. 45%, respectively, P = 0.002). Concordant FPG levels ≥7.0 mmol/l (currently recommended for diagnosis) occurred in only 19% of our cohort with type 2 diabetes. CONCLUSIONS—Diagnostic criteria based on FPG criteria are relatively insensitive in the detection of early type 2 diabetes in at-risk subjects. HbA1c measurement improves the sensitivity of screening in high-risk individuals.